Konstruktion von Sprache und Sprachwissen Eine empirische Studie zur Schriftsprachaneignung sprachstarker und sprachschwacher Kinder - Schaller, Pascale (Reihe Germanistische Linguistik, 2018)
This study examines the empirical differences between children with strong and weak language skills in the area of written language acquisition. While learning age has been extensively studied by researchers as the critical factor in variation between individuals, this study also considers global language competence. In conducting the study, the author used standardized language level measurements, psychological tests, and questionnaires.